2018
DOI: 10.1002/brb3.942
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of brain anatomical patterns by comparing region intensity distributions: Applications to the description of Alzheimer's disease

Abstract: PurposeThis work presents an automatic characterization of the Alzheimer's disease describing the illness as a multidirectional departure from a baseline defining the control state, being these directions determined by a distance between functional‐equivalent anatomical regions.MethodsAfter a brain parcellation, a region is described by its histogram of gray levels, and the Earth mover's distance establishes how close or far these regions are. The medoid of the control group is set as the reference and any bra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 55 publications
(86 reference statements)
0
13
2
Order By: Relevance
“…The proposed CNN model has the best performance in terms of accuracy values for diagnosis of MCI. The other study [11] reported a 0.74 AUC value, which is higher than the 0.6 AUC value of the proposed CNN model. However, the feature engineering applied in the other study [11] should be evaluated carefully while comparing the performance of the two studies.…”
Section: Comparison With Other Studiescontrasting
confidence: 60%
See 4 more Smart Citations
“…The proposed CNN model has the best performance in terms of accuracy values for diagnosis of MCI. The other study [11] reported a 0.74 AUC value, which is higher than the 0.6 AUC value of the proposed CNN model. However, the feature engineering applied in the other study [11] should be evaluated carefully while comparing the performance of the two studies.…”
Section: Comparison With Other Studiescontrasting
confidence: 60%
“…They did not provide an accuracy value for model performance. Although the proposed CNN model has a lower AUC value (0.85) compared to the study by Giraldo et al [11] (0.92), the proposed model does not explicitly extract MRI features (i.e. brain parcellation process on MRI); instead it uses automatically computed features provided by convolutional and pooling layers of the CNN model.…”
Section: Comparison With Other Studiesmentioning
confidence: 77%
See 3 more Smart Citations